Changes in Mood States Are Induced by Smelling Familiar and Exotic Fragrances - Sarid, Orly; Zaccai, Michele (Frontiers in Psychology, 2016)
Abstract Familiar fragrances usually induce positive mood states and elicit favorable evaluation. Relaxation is also widely thought to improve mood state. Yet experimental evidence on the effect of two different stimuli, fragrance smelling and breathing relaxation, on mood state and fragrance evaluation is lacking. This study aimed to test (1) the effect of two familiar fragrances, lavender and myrtle, and two exotic fragrances, bergamot and ravensara, on perceived mood states before and after relaxation, (2) the effect of relaxation on perceived mood states for each fragrance, and (3) the effect of relaxation on fragrance evaluation as defined by adjectives. We hypothesized that mood states and assessment of the fragrances would differently be affected both in familiar vs. non-familiar fragrances and also before and after relaxation. Participants (n = 127) completed questionnaires on their mood states at baseline (T0). They were then presented with each of the four fragrances separately and asked to report on mood state and to assess the fragrances with adjectives before (T1) and after (T2) breathing relaxation. Analyses of the T0−T1 delta values of mood states by ANOVA repeated measures and post hoc comparisons showed that mood states were affected by fragrance smelling with no clear differences observed between familiar and exotic fragrances. The same analyses of T1−T2 values showed no differences in mood state after breathing relaxation and fragrance smelling. Fragrance assessment by adjectives indicated a non-conclusive trend for familiar and exotic fragrances. In sum, mood states induced by the fragrance smelling stimulus (T0−T1) were not changed by the addition of the second stimulus of relaxation (T1−T2), indicating that the former stimulus was stronger than the latter. On the other hand, the cognitive component represented by adjective-based assessment of fragrances was slightly modified by the relaxation stimulus.